Obesity and hypothyroidism (Ожирение и метаболизм, 2013)
Obesity and hypothyroidism are common diseases, and consequently clinicians should be particularly alert to the possibility of thyroid dysfunction in obese patients. The relationship between thyroid function and obesity is likely to be bidirectional, with hypothyroidism affecting weight, but obesity also influencing thyroid function. Both serum thyroid-stimulating hormone and fT3 are typically increased in obese individuals, an effect likely mediated by leptin. Following L-T4 treatment for overt hypothyroidism, weight loss appears to be modest and mediated primarily by loss of water weight rather than fat. Selected thyroid analogs might be a means by which to improve weight loss by increasing energy expenditure in obese patients during continued caloric deprivation